A study on computer programmes applied for solar simulation in architecture and urban design - Mazloomi, Mehrdad; Hassan, Ahmad Sanusi (2008)
This paper conducts a study on the computer programmes which are applied to simulate solar radiation in research area of urban development and architecture. These programmes are useful to simulate thermal behaviour of a building or its envelope when they are exposed to the sun. The other benefit in application of these programmes is to understand influence of solar irradiation on energy efficiency for buildings as well as identifying comfort level for pedestrians walking in cities. Since these programmes are released in an immense range, hence this paper attempts to introduce several of well-known programmes that are available in the market and widely used by those involved in related research with this study. In addition, the paper’s effort is not only introducing the simulator, but also to clarify the strong and weak points of the programmes. Subsequently, limitation in terms of availability of either programme is shown and rate of required expertise is discussed in its relevant section of this paper. At the end their capabilities are compared together and comprehensiveness of alliances within programmes is pointed out.